Entrepreneurial Intention Measurement Model in the Context of Assessment for Learning - Utami, Mutiara Arlisyah Putri; Taufiq, Taufiq; Syamsuddin, Syaiful (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Entrepreneurial intention is an important factor in the success of entrepreneurs as a solution to reduce unemployment. The main urgency of this research is that currently there is no measurement instrument to assess students’ entrepreneurial intentions, especially during the entrepreneurship learning process. However, such an instrument is important as a simulation tool to determine learning models that can increase entrepreneurial intentions. The purpose of this study was to develop a measurement model of entrepreneurial intentions that serves both as an assessment tool and a simulation for determining the entrepreneurial learning approach aimed at increasing these intentions. This research used the Borg & Gall model, obtaining primary data by distributing questionnaires to 224 respondents using purposive sampling, which refers to the rule of thumb. The data was analyzed using face validity by expert judgment and then the items of the Pearson item-total correlation instrument were analyzed with results of a correlation coefficient of > 0.3 and a reliability value of 0.905 or > 0.80 with a high level of confidence. Construct validity analysis used Confirmatory Factor Analysis and Second Order CFA with three goodness of fit criteria, namely χ² (chi square) value 0.18 or < 0.05; p-value 0.67 or > 0.05; CFI (Comparative Goodness of Fit index) 1.00 or > 0.9; and RMSEA (Root Mean Square Error of Approximation) 0.000 or < 0.08. The results show that the model formed fits with acceptable criteria. Five factors were identified from the measurement model, namely entrepreneurial motivation, self-efficacy, entrepreneurial education, independence, and internal locus of control.